2007
DOI: 10.1097/pec.0b013e31814a6a95
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Magnesium Sulfate for Treatment of Ventricular Tachycardia in Amitriptyline Intoxication

Abstract: In our country, tricyclic antidepressants are usually present in most of the homes. Myocardial depression and ventricular arrhythmia are the severe side effects in tricyclic antidepressant overdose. A 4-year-old boy was brought to our hospital after taking 70 mg/kg of amitriptyline. On arrival, the patient was comatose (Glasgow Coma Score was 3), had a shallow breathing pattern with bradycardia (HR <30/min), and hypotension. He was intubated and resuscitated with multiple doses of adrenaline and sodium bicarbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…1 , 11 The most important cause of death is persistent hypotension resulting from myocardial depression due to arrhythmias. 3 , 5 , 10 , 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 , 11 The most important cause of death is persistent hypotension resulting from myocardial depression due to arrhythmias. 3 , 5 , 10 , 12 , 13 …”
Section: Discussionmentioning
confidence: 99%
“…Various methods have been used to treat patients with severe cardiotoxicity due to amitriptyline overdose. These include serum alkalinisation with hypertonic NaHCO 3 20 or hyperventilation, 21 inotropic agents, 4 , 22 magnesium sulphate, 5 anti-arrhythmic drugs, 2 , 14 glucagon 12 haemoperfusion, 23 , 24 or lipid emulsion. 25 Although many studies have compared these treatment methods, no treatment has been shown to prevent or reduce the toxicity in patients who may potentially develop severe toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been used successfully in the treatment and prevention of various atrial and ventricular arrhythmias, torsades de pointes and in stabilising cardiac repolarisation in heart failure 9. Moreover, in cardiac toxicity (wide QRS, prolonged QT) due to tricyclic antidepressant overdose, which is largely mediated by class 1A antiarrhythmic effect (sodium channel blockade), magnesium has been found to be very effective in treating intractable arrhythmias 10. As a calcium-channel antagonist, magnesium sulphate may have the potential to worsen hypotension and atrioventricular block and its administration must be carefully considered.…”
Section: Discussionmentioning
confidence: 99%